The Effect of Leadership and Work Environment on Employee Performance Through Mediation of Work Spirit at Prama Sanur Beach Hotel - Ni Wayan Anggreni; Ni Wayan Sitiari; Putu Indiani (Jurnal Ekonomi dan Bisnis Jagaditha, 2018)
Abstract-Performance is the achievement or outcome of work (output) in the form of quality and quantity that has been achieved by human resources per unit of time period in carrying out its work duties that is in accordance with the responsibilities assigned. Leadership is an activity to influence the behavior of human either individual or group and/or art. The study was conducted at Prama Sanur Beach Hotel. It addresses the influence of leadership and work environment on employee performance through mediation of work spirit. Participants in this study were 81 persons of 417 employees of Prama Sanur Beach Hotel. We distributed questionnaires containing questions to identify the employee perception toward leadership system realized in their work place. We also collected a number of other related sources and theories to leadership and mediation of work, such as books, documents from library. We tested the hypothesis by Partial Least Square (PLS) application. The results showed that: (1) leadership and work environment have a positive and significant effect on employee work spirit; (2) work environment and the spirt of work positively and significantly affect the employee performance; (3) employee spirit of work can fully mediate between leadership and performance; and (4) employee spirit of work can mediate between the work environment and employee performance. Keywords: Leadership; Work Environment; Working spirit and Performance.